Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa Di Kecamatan Sedati Kabupaten Sidoarjo - Amelia, Neneng Musyrifatul; Hidayat, Muhammad Taufiq (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This research was conducted in connection with Accountability for Management of Village Fund Allocations in Sedati District, Sidoarjo Regency. The aim of this research is to determine and analyze the application of the principle of Accountability in managing Village Fund Allocations in the Five Villages in Sedati District, Sidoarjo Regency. This type of research uses qualitative methods with a descriptive approach. The data sources used are primary data sources and secondary data sources. Researchers analyzed data by means of data transcription, source triangulation, and data reduction. The stages that researchers carried out started from observation, interviews, and documentation. The data processing process uses data transcription, source triangulation, data reduction, and drawing conclusions. Data analysis for managing Village Fund Allocations has five stages, namely planning, implementation, administration, reporting and accountability. The results of this research show that all stages in the management of Village Fund Allocations have run well in accordance with the principles of Accountability and PERMENDAGRI Number 20 of 2018 concerning village financial management.